Perspectives on Designing Design Managers By Lee D. Green, Jeff Smith, Gary Bryant, Rachel Cooper, Kyung‐Won Chung, and Maryann Finiw. (December 2014) - Nussbaum, Bruce
<x xml:space="preserve">Abstract</x> The strongest and strangest rift in academia is perhaps between business and design. For two fields that are so interdependent on one another, the separation is appalling—and completely unnecessary. In the world of fashion, for example, designers know they must be creators (each season, twice a year, year after year), as well as manufacturers, originators and retailers, loners and team players, empathizers and pathbreakers. By the time they are seniors, fashion students know where to outsource, who to go to for publicity and marketing, what margins are needed to stay in business. Nearly all have been required to intern in successful fashion businesses and have learned the realities of the fashion world from the ground up. In the best fashion schools, from Parsons in New York to Central Saint Martins in London, this is what professors teach and what the curriculum is composed of. Yet in this article, we clearly see that other design schools are not doing this job. Designers graduate without the abilities to function in a business environment, much less build a new business. This is a tragedy with a cause—bad design education. What is needed to be great corporate designers and design managers? The deepest need is understanding—not of the customer, but of business itself. Learning the language and values of business and integrating them into the designer's practice and presentation is the key to success. What is valuable? How is it measured? How can you deliver it? These are all key questions. Designers need to know not only their own process but also the process of bringing their creations to the marketplace. This is what unites such an unlikely pair of designers as Alexander McQueen and Jonathan Ive. One made incredible clothes; the other makes incredible consumer electronics. Yet both obsessed over materials, manufacturing, marketing, and price. This is what designers have to learn to either be part of a team or lead one. It isn't magic.